The Optimization of Teacher Performance Through The Quality of Principal Leadership in Public Senior High School. - Sumarni Rumfot; Riska Arnas; Susanto Susanto; Yusuf Muchtar; Nur Rahmah Wahyuddin (Departement of Mathematics Education, 2023)
The purpose of this study is to describe teacher performance, to describe the leadership of the principal, to describe efforts to optimize teacher performance through the leadership of the principal in one of the public high schools in South Tangerang City. This research uses a type of qualitative research with descriptive methods. Descriptive method is a type of research that describes and answers the problems of a phenomenon or event that is happening at this time. The focus of this research is to explain the optimization of teacher performance through the principal's leadership. In accordance with the nature and characteristics of qualitative research, this study produces qualitative data that reveals phenomena in the environment through the speech and behavior of people or study subjects. This research is not intended to examine variables so that the approach used in this technique uses interviews, observations, and document studies. Data analysis is changing the processed data into something that has meaning for researchers and readers of research reports. Teacher performance, which includes learning, implementation of guidance, and professional development, has shown good quality. Teachers have high awareness to carry out their duties and roles in school. In the learning aspect, each teacher develops and owns learning tools, such as annual programs, semester programs, syllabus, and lesson plans (RPP). In the implementation of learning, of course, it refers to the learning plans that have been made and learning assessments, of course, looks at the process and learning outcomes, as well as students' knowledge and skills. In the aspect of guiding abilities, each teacher guides students.